2016
DOI: 10.3727/096368916x690782
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Recombinant GABAergic Cells in a Model of Peripheral Neuropathic Pain

Abstract: Chronic neuropathic pain represents a clinically challenging state with a poor response to current treatment options. Long-term management of chronic pain is often associated with the development of tolerance, addiction, and other side effects, reducing the therapeutic value of treatment. Alternative strategies based on cell therapy and gene manipulation, balancing the inhibitory and excitatory events in the spinal cord, may provide sustained pain relief in the long term. Transplantation of GABAergic cells has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…One thousand seven hundred twenty one studies were excluded by screening the titles and abstracts and the full texts of the remaining 39 were studied (Appendix 2). Finally, the data of 13 studies were included in the present meta-analysis [ 15 , 16 , 22 - 32 ] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One thousand seven hundred twenty one studies were excluded by screening the titles and abstracts and the full texts of the remaining 39 were studied (Appendix 2). Finally, the data of 13 studies were included in the present meta-analysis [ 15 , 16 , 22 - 32 ] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The route of administration was also evaluated in in the present study. Overall, the method of injection was intraspinal in nine studies [ 15 , 22 - 24 , 26 , 27 , 29 , 30 , 32 ] and intrathecal in three studies, while one study had transplanted the cells in the anterior cingulate cortex. Overall, the analyses revealed that the intraspinal administration method might be the desired route for the transplantation of GABAergic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells were then transplanted onto an injury site in order to assess their effect on peripheral neuropathic pain after 1 week of induced injury in rat spinal cord. This transplant resulted in improved pain sensitivity based upon a pain-related behavioral assessment with four pain parameters: mechanical, heat, cold, and tactile [ 143 ]. Similarly, Mery et al engineered pacemaker cells from embryonic stem cells that induce InsP3 mediated oscillatory calcium release from the endoplasmic reticulum; these cells had a potential to serve as pacemaker cells prior to the development of pacemaker ionic channels in early embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the naturally occurring peptide histogranin (Lemaire et al, 1993 ) and its stable analog Serine-Histogranin (SHG) have NMDA receptor antagonist activity and do not interfere with locomotion (Lemaire et al, 1995 ; Prasad et al, 1995 ; Hama et al, 1999 ; Hama and Sagen, 2002 ; Hentall et al, 2007 ). Furthermore, data has shown marked attenuation of hyperalgesia and allodynia with the spinal introduction of SHG through intrathecal injection or via cell or gene therapy (Siegan et al, 1997 ; NasiriNezhad and Sagen, 2005 ; Gajavelli et al, 2008 ; NasiriNezhad et al, 2015 ; Jergova et al, 2016a , b ).…”
Section: Introductionmentioning
confidence: 99%